Some Surface and Catalytic Properties of VO–CrO/SiO, MoO–CrO/SiO and NiO–CrO/SiO Ternary Solid Catalysts - A.M. Youssef; A.I. Ahmed; S.E. Samra; N.B. El-Assy; E.A. El-Sharkawy (Adsorption Science & Technology)
Ternary vanadia–chromia/silica, molybdena–chromia/silica and nickel oxide–chromia/silica solid catalysts were prepared by the impregnation method. Their structural characteristics were examined using differential thermal analysis (DTA) and X-ray diffraction techniques. The catalytic activities of the prepared samples towards the conversion of isopropanol and cyclohexanol and the kinetics of these catalytic conversions were studied with the aid of a microcatalytic pulse technique. In addition, the surface acidities of selected samples were measured from the percentage of propene produced by the poisoned catalysts. X-Ray diffraction and differential thermal analysis revealed that the only detectable phase was α-Cr 2 O 3 with the presence of all other phases or spinel not being confirmed. The order of the surface acidities was found to lie in the sample sequence: 3 wt% V 2 O 5 –20 wt% Cr 2 O 3 /SiO 2 > 3 wt% MoO 3 –20 wt% Cr 2 O 3 /SiO 2 > 20 wt% Cr 2 O 3 /SiO 2 > 3 wt% NiO-20 wt% Cr 2 O 3 /SiO 2 , all samples having been precalcined at 500°C. Catalytic conversion of isopropanol gave propene and acetone, whereas cyclohexene, cyclohexanone and methylcyclopentene (as an isomerization product) were produced from the catalytic conversion of cyclohexanol. The catalytic activity was found to be influenced considerably by the type of impregnating ion employed and by the precalcination temperature, and hence by the surface acidity of the examined catalysts. On the other hand, the Bassett–Habgood and Kiperman equations could be applied in a satisfactory manner to the generation of the various reaction products. The calculated activation energies for the catalytic conversion of isopropanol and cyclohexanol were compared.